PROGNOSTIC VALUE OF LIPOPROTEIN(A) FOR MAJOR ADVERSE CARDIOVASCULAR EVENTS IN RELATION TO C-REACTIVE PROTEIN - A SYSTEMATIC REVIEW AND META-ANALYSIS - Pamela L. Alebna, MD, MPH (Elsevier, 2024)
Therapeutic Area: ASCVD/CVD Risk Factors Background: Existing evidence supports an increased risk of Major Adverse Cardiovascular Events (MACE) with elevated lipoprotein(a) (Lp(a)) regardless of high sensitivity C-reactive protein (hs-CRP) levels. However, some studies have presented divergent results between primary and secondary prevention populations. A meta-analysis could yield a more definitive estimation of the joint influence of these biomarkers on MACE risk. Methods: We performed a systematic review of studies evaluating the risk of MACE with elevated Lp(a) and hs-CRP (PROSPERO CRD4202345109). The primary outcome was the pooled hazard ratio (HR) of the association between Lp(a) and MACE among individuals with low (<2mg/L) and high (≥2 mg/L) hs-CRP levels. We performed a subgroup analysis in primary and secondary prevention populations. A random effects model was used given the wide heterogeneity in studies. Results: A total of seven studies were identified in the systematic review and included in the meta-analysis. The overall pooled sample comprised 558,914 individuals. The mean proportion of females was 37% and the weighted mean age for the entire cohort was 58.9 years. In individuals with elevated Lp(a), the risk of MACE was significantly increased across both low and high hs-CRP groups, with pooled hazard ratios (HR) of 1.24 (95% CI: 1.10-1.41) and 1.33 (95% CI: 1.19-1.49), respectively. In the primary prevention population, the pooled HR for low and high hs-CRP groups was 1.33 (95% CI: 1.06-1.66) and 1.43 (95% CI: 1.13-1.82), respectively, with a nonsignificant subgroup difference (P=0.65). The corresponding HR for the secondary prevention population was 1.10 (95% CI: 1.03-1.18) and 1.31 (95% CI: 1.09-1.57), respectively, with a non-significant subgroup difference (P=0.34) (Figure). Conclusions: Our analysis confirms that elevated Lp(a) significantly elevates MACE risk across varying hs-CRP levels, underlining its relevance in both primary and secondary prevention cohorts.